Overview of General and Discriminating Markers of Differential Microglia Phenotypes - Jurga, Agnieszka M.; Paleczna, Martyna; Kuter, Katarzyna Z. (Frontiers in Cellular Neuroscience, 2020)
Inflammatory processes and microglia activation accompanies most of the pathophysiological diseases in the central nervous system. It is proven that glial pathology precedes and even drives development of multiple neurodegenerative conditions. A growing number of studies point out the importance of microglia in brain development as well as in the physiological functioning. Those resident brain immune cells are divergent from the peripherally infiltrated macrophages, but their precise in situ discrimination is surprisingly difficult. Microglia heterogeneity in the brain is visible especially in their morphology, cell density in particular brain structures, but also in the expression of cellular markers. This often determines their role in physiology or pathology of brain functioning. The species differences between rodent and human markers add complexity to the whole picture. Furthermore, due to the activation, microglia shows a broad spectrum of phenotypes ranging from the pro-inflammatory, potentially cytotoxic M1, to the anti-inflammatory, scavenging and regenerative M2. A precise distinction of specific phenotypes is nowadays essential to study the microglial functions and tissue state in such quickly changing environment. Due to the overwhelming data on multiple sets of markers available for the studies, the choice of appropriate markers is a scientific challenge. This review gathers, classifies and describes known and recently discovered protein markers expressed by microglial cells in their different phenotypes. Presented microglia markers include qualitative and semi-quantitative, general and specific, surface and intracellular proteins as well as secreted molecules. Information provided here creates a comprehensive and practical guide trough the current knowledge and will allow to choose proper, more specific markers for the detailed studies on microglia and neuroinflammatory mechanisms in various, physiological, as well as pathological, diseases and conditions. Both, basic research and clinical medicine, need clearly described and validated molecular markers of microglia phenotype, essential in diagnostics, treatment and prevention of diseases engaging glia activation.